2021
DOI: 10.1186/s12872-021-02055-w
|View full text |Cite
|
Sign up to set email alerts
|

Echocardiographic left ventricular geometry profiles for prediction of stroke, coronary heart disease and all-cause mortality in the Chinese community: a rural cohort population study

Abstract: Background The utility of echocardiographic left ventricular (LV) geometry in the prediction of stroke/coronary heart disease (CHD) and all-cause mortality is not well characterized. This study aimed to evaluate the overall and sex-specific prognostic value of different geometric patterns on the incidence of stroke/CHD and all-cause mortality in a Chinese population-based cohort. Methods We conducted a prospective study in the general population in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 39 publications
1
11
1
1
Order By: Relevance
“…End-diastolic (d) and end-systolic (s) LV internal diameters (LVID), interventricular septum (IVS) thickness and posterior wall (PW) thickness were measured off-line from two-dimensionally guided M-mode tracings recorded at 50-100 cm/s speed, during at least three consecutive cycles. LV mass was estimated using the corrected ASE method: 0.8x(1.04x[(IVSd + LVIDd + PWTd) 3 -LVIDd 3 ]) + 0.6 and normalized to body surface area. (BSA).…”
Section: Echocardiographymentioning
confidence: 99%
See 2 more Smart Citations
“…End-diastolic (d) and end-systolic (s) LV internal diameters (LVID), interventricular septum (IVS) thickness and posterior wall (PW) thickness were measured off-line from two-dimensionally guided M-mode tracings recorded at 50-100 cm/s speed, during at least three consecutive cycles. LV mass was estimated using the corrected ASE method: 0.8x(1.04x[(IVSd + LVIDd + PWTd) 3 -LVIDd 3 ]) + 0.6 and normalized to body surface area. (BSA).…”
Section: Echocardiographymentioning
confidence: 99%
“…Marfan's and Ehlers-Danlos syndromes) or atherosclerotic diseases [1]. Unlike most echocardiographic measures of cardiac structure [2][3][4][5], however, the value of aortic diameter for the stratification of cardiovascular risk in populations free from overt aortic disease is still poorly defined due to the fact that the association of aortic diameter with cardiovascular events and death relies on few longitudinal studies carried out in heterogeneous populations, based on different definitions of the aortic phenotypes and characterized by relatively short follow-ups [6][7][8][9][10]. These are the main reasons why the 2018 European Society of Cardiology/ European Society of Hypertension (ESC/ESH) guidelines did not include aortic diameter among the markers of cardiac damage to be considered in hypertensive patients [5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In prospective studies, the left ventricular geometry has been identified as an adverse cardiovascular prognostic factor 1 , 2 . There are four distinct left ventricular geometries according to the American Society of Echocardiography: normal (NL), concentric remodeling (CR), concentric hypertrophy (CH), and eccentric hypertrophy (EH) 3 .…”
Section: Introductionmentioning
confidence: 99%
“…Ухудшение прогноза и повышение риска сердечно-сосудистых осложнений (ССО) у больных ИБС с сопутствующей АГ в существенной степени связаны с изменением геометрии, структуры и массы левого желудочка (ЛЖ), а также с возрастом, полом и сопутствующими заболеваниями [5,6]. Очевидно, что вопрос анализа предикторов ССО у больных ИБС и АГ представляется весьма актуальным и нуждается в более детальном обсуждении [2,4,7,8].…”
unclassified